A Comparative Analysis of Island vs. Mainland Arthropod Communities in Coastal Grasslands Belonging to Two Distinct Regions: São Miguel Island (Azores) and Mainland Portugal - Calado, Hugo Renato M. G. (2024)
Coastal grasslands host diverse arthropod communities and provide important ecosystem services. Islands, being isolated environments, are expected to have simpler ecosystems than continental areas, with the few successful colonizing species often attaining high densities; however, these patterns are still poorly documented for coastal grassland arthropods. We conducted a comparative study of the biodiversity of arthropod communities in two distinct coastal grassland ecosystems (Portugal mainland and the Azores) with the following objectives: (a) to investigate the arthropod community composition in both locations; (b) to compare the diversity profiles in both locations; (c) to investigate potential density compensation in the island’s arthropod communities. For four months, arthropods were collected on the Island of São Miguel, Setúbal Peninsula, and Sine’s region and subsequently classified into taxonomic groups. With the data collected, Hill Numbers were calculated for each region. We confirmed that the richness on the mainland was higher than in the Azores, and we found some apparent abundance compensation in the Azores. At the same time, we also observed that many species in the Azores are also present in the continental coastal grasslands of mainland Portugal.